Incidence and severity of malreduction of the tibiofibular syndesmosis following surgical treatement of displaced ankle fractures and impact on the function –Clinical study and MRI evaluation. Issue 6 (June 2018) - Ntalos, D.; Rupprecht, M.; Grossterlinden, L.G.; Hamurcu, A.; Regier, M.; Klatte, T.O.; Rueger, J.M.; Spiro, A.S.
Abstract: Purpose: To compare tibiofibular reduction quality in different types of operatively treated ankle fractures and the impact on clinical and functional outcome at mid-term follow-up. Patients and methods: One hundred patients with an acute ankle fracture who had undergone open reduction and internal fixation were included. Eighty-eight patients who suffered from ligamentous ankle injury with neither fracture nor syndesmotic lesions served as a control group. Tibiofibular alignment was measured on MR images in all 188 patients. In case of tibiofibular malreduction tibiotalar positioning was determined as well. Clinical and functional outcome was assessed using the AOFAS hindfoot score as well as the SF-36. Results: No tibiofibular malreduction was found in type Weber B fractures, irrespective of syndesmotic instability followed by syndesmotic screw placement, as compared to the control group. A significant tibiofibular malreduction was detected in bimalleolar/trimalleolar/dislocated type Weber B fractures and in isolated type Weber C fractures with syndesmotic screw, in comparison to the control group. Tibiotalar displacement could not be detected. Clinical and functional outcome analysis revealed no significant differences between the treatment groups. Conclusion: Three-dimensional imaging may improve tibiofibular malreduction visualization in bimalleolar/trimalleolar/dislocated type Weber B fractures and in isolated type Weber C fractures with syndesmotic transfixation. The clinical impact of improving tibiofibular positioning remains highly questionable since there was no correlation between tibiofibular alignment and the clinical outcome at mid-term follow-up.